2009
DOI: 10.1159/000211718
|View full text |Cite
|
Sign up to set email alerts
|

Environmental and Individual Factors Associated with Nail Fluoride Concentration

Abstract: Nails have been suggested as suitable biomarkers of exposure to F, with the advantage of being easily obtained. The effect of water F concentration, age, gender, nail growth rate and geographical area on the F concentration in the fingernail and toenail clippings were evaluated. Volunteers (n = 300) aged 3–7, 14–20, 30–40 and 50–60 years from five Brazilian communities (A–E) participated. Drinking water and nail samples were collected and F concentration was analyzed with the electrode. A reference mark was ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 26 publications
(30 reference statements)
2
26
1
1
Order By: Relevance
“…However, this occurs at the long term, i.e. it is possible to see a significant increase in nail fluoride concentration of 3-to 7-year-old children compared with 30-to 40-year-old or 50-to 60-year-old volunteers, but not with 14-to 20-year-old volunteers [Fukushima et al, 2009]. Thus, it is unlikely that this small variation in the age range of the volunteers (2-3 vs. 6-7 years of age) might have influenced the results of this study.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…However, this occurs at the long term, i.e. it is possible to see a significant increase in nail fluoride concentration of 3-to 7-year-old children compared with 30-to 40-year-old or 50-to 60-year-old volunteers, but not with 14-to 20-year-old volunteers [Fukushima et al, 2009]. Thus, it is unlikely that this small variation in the age range of the volunteers (2-3 vs. 6-7 years of age) might have influenced the results of this study.…”
Section: Discussionmentioning
confidence: 95%
“…It is important to mention that there was a small variation in the age range of the volunteers included in the present investigation (2-7 years) ( table 1 ), since they were recruited among participants of previous studies with different designs. It has been shown that nail fluoride concentration is expected to increase with age [Fukushima et al, 2009] as a conse- quence of an increase in plasma fluoride concentration [Buzalaf and Whitford, 2011] . However, this occurs at the long term, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As only the absorbed fluoride is implicated in fluorosis development, measurement of total exposure through analysis of body fluids or tissues is more likely to be of value in epidemio- M ean annual temperatures in the communities located in the Northeast region are higher than in those located in the Southeast. In general, residents of B, D and E have monthly incomes similar to each other, but approximately half and one third the income of A and B, respectively (data from Fukushima et al [2009]). …”
Section: Discussionmentioning
confidence: 99%